Bioplastic from Jackfruit Seed Starch and It Is Potency for Education for Sustainable Development (ESD) in Chemistry Learning - Purba, Ester Yuliati Cristina; Hernani, Hernani; Supriatna, Asep (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2024)
Plastic waste is a severe environmental problem. One solution is with bioplastic from jackfruit seed starch (JS). However, this bioplastic has weaknesses, such as not being heat resistant and having low mechanical properties, so adding chitosan (CH) and glycerol is necessary to strengthen it. This study aims to determine the optimum conditions for making bioplastics from jackfruit seed starch (JS) with the addition of chitosan (CH) and its potential in ESD-oriented chemistry learning. The methods used were laboratory experiments to determine the optimum conditions for making bioplastics, and an open-ended questionnaire to determine the potential of bioplastics as an ESD-oriented chemistry learning topic. The results of this study obtained tensile strength A1 (0.904 MPa), A2 (0.669 MPa), A3 (0.541 MPa), A4 (0.618 MPa), A5 (1.357 MPa), and A6 (6.140 MPa). The elongation test resulted in A1 (15.8%), A2 (16.5%), A3 (23.7%), A4 (35.7%), A5 (58.1%), and A6 (40.1%). The addition of chitosan increases the tensile strength and elongation values of bioplastics. The A3 and A4 bioplastics biodegradation tests were optimally decomposed within 5 days with a mass loss of 94%. Questionnaire results from 40 students showed that the topic of bioplastics has the potential to be integrated with project-based ESD lectures. Thus, bioplastic making can be used as one of the chemistry learning topics in project-based ESD lectures.